Assessment of microbial quality of water in popular restaurants in Sylhet city of Bangladesh (Bangladesh Journal of Agricultural Research, 2016)
Microbial contaminations of drinking water constitute a major burden on human health. Interventions to improve the quality of drinking-water provide significant benefits to health. An assessment of microbial quality of water in the samples obtained from different popular restaurants of Sylhet City Corporation, Bangladesh were analyzed in the laboratory. Our aims were to find out the microbial properties of water, to analyze the potable water qualities of the restaurants and also to compare it with different standards to assess the health risk of people. The microbial tests viz. MPN, TVC and total coliform test were studied. Results revealed that all the water samples were fecal contaminated and had a great chance of contamination by other pathogenic bacteria. Results indicated that most of the samples were significantly positive to MPN test and TVC bacteria were highly significant. The risk score for coliform bacteria also remarked high risk for human health according to WHO standards and were not suitable as potable water. Our recommendations are therefore, water supply authority including restaurant owners should take necessary steps for the maintenance of microbial quality of water and microbial assessments should be done very often to leading a hygienic water distribution environment of the city.Bangladesh J. Agril. Res. 41(1): 115-125, March 2016